Exchange rate pass-through and cross-country spillovers: Some evidence from Ukraine and Russia - Oleksandr Faryna (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
​This paper studies exchange rate pass-through to consumer prices in Ukraine and Russia considering cross-country linkage and spillover effects. We relax the assumption of "isolated islands" and employ a bilateral panel VAR (BPVAR) approach to estimate a pass-through effect from the ruble to hryvnia exchange rate (UAH/RUB) movements, taking into account cross-unit hetero-geneities as well as dynamic and static interdependencies. We then compare BPVAR estimates with those from individual VAR models and find that, while results for Russia do not change significantly, spillover effects are identified for Ukraine. In particular, ruble depreciation (e.g. hryvnia appreciation) results in increasing Ukrainian prices instead of declining as suggested by individual VAR analysis. We also estimate alternative BPVAR including hryvnia and ruble ex-change rates with respect to the US dollar and find that prices in Ukraine respond to changes in USD/RUB to a larger extent than to UAH/USD.
URN:NBN:fi:bof-201610071440
Keywords: E31; E52; E58; 330